Saussurean Semiotic Analysis of Visual Meme Literal Wordplay - Assyifa Putri Azzahra; Ujang Suyatman; Deni Suswanto (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the linguistic-semiotic mechanisms in visual memes featuring literal wordplay in English. The data consist of five visual memes, Butterfly, Catfish, Eggplant, Fireworks, and Bookworm, collected from digital platforms such as Google Images, Pinterest, and Facebook. This study employs a descriptive qualitative approach, using Ferdinand de Saussure’s semiotic theory as the primary framework, alongside Victor Raskin’s Script-based Semantic Theory of Humour (SSTH). The results show that memes break words down into their literal elements and visualize them, thereby creating a clash between conventional meaning and literal-visual meaning, emphasizing the arbitrary nature of signs in language and triggering incongruity that produces a humorous effect. This study contributes to linguistic semiotics by emphasizing that the arbitrariness of signs is not just a theoretical concept, but an active mechanism that enables the reinterpretation of meaning in language.